In-Vivo Analgesic And Anti-Inflammatory Effects Of Eel (Anguilla bicolor bicolor) Oil - Heru Sasongko; Nur Indria Kusumastuti; Gea Ros Alifa; Aulia Ayu Rahmawati (Universitas Ahmad Dahlan, 2019)
Analgesic and anti-inflammatory tests of eel (Anguilla bicolor bicolor) oil on animal models have been performed. Previous studies have proven that oral administration of EPA and DHA exhibits analgesic and anti-inflammatory effects. Gas Chromatography analysis shows that eel contains EPA and DHA. In this research, the analgesic activity was evaluated with the acetic acid-induced writhing test and hot plate test, while the anti-inflammatory properties were identified using carrageenan-induced inflammation. In the writhing test, 25 male Swiss Webster mice were divided into five groups. Group I was given 0.5% CMC-Na as a negative control, group II was given 65 mg/kg b.w. of Acetosal as a positive control, group III-V was given eel oil at different doses, namely 2400, 4800, and 9600 mg/kg b.w. of the mouse. For the hot plate test, 6.5 mg/kg b.w. of tramadol acted as the positive control. Similar to the analgesic effect analysis, the anti-inflammatory test also divided 25 male Wistar rats into five groups. Group I as a negative control was given 0.5% CMC-Na, Â group II was given 9 mg/kg b.w. of diclofenac potassium as a positive control, and group III-V were given eel oil at different doses, namely 1500, 3000, and 6000 mg/kg b.w. of the rat. The results of the acetic acid-induced writhing test and hot plate test showed that when compared with the positive and negative controls, eel oil had a potential analgesic activity with a significance value of p< 0.05. The analgesic effects were noticeable at doses of 2400, 4800 and 9600 mg/kg b.w. in the writhing test and at 4800 and 9600 mg/kg b.w. in the hot plate test. The anti-inflammatory test showed that eel oil was efficacious when administered at the doses of 1500, 3000, and 6000 mg/kg b.w. with percentage inhibition of 34.35%, 35.132%, and 40.28%, respectively.Â